مقارنة بين الإجراءات العلاجية المتبعة في علاج الشق الشرجي المزمن - حاج قاسم, فؤاد; دبرها, محمود; سعيد, أيهم (Latakia University Journal -Medical Sciences Series, 2019)
شملت هذه الدراسة 118 مريضا ً قبلوا وعولجوا في قسم الجراحة في مشفى الأسد الجامعي باللاذقية، 76 أنثى (64.4%) و42 ذكراً (35.6%). توضعت الشقوق في الأماكن التالية: خلفي 106 مرضى (89.8%)، أمامي 11 مريضاً (9.3%)، وفي المكانين معاً 1 مريض (0.8%). تم تقسيم المرضى إلى مجموعتين: الأولى: عولجت جراحياً وضمت 68 مريضاً، والثانية: عولجت بحقن الـ BOTOX وضمت 50 مريضاً. كما تم تقسيم المجموعة الثانية إلى قسمين: الأول عولج بحقن 10 وحدات دولية وشمل 30 مريضاً، والثاني: عولج بحقن 20 وحدة دولية وشمل 20 مريضاً. كان هدف هذه الدراسة المقارنة بين طرق علاج الشق الشرجي المزمن من أجل انتقاء العلاج الأكثر فعالية والأقل من حيث الخطورة والمضاعفات. This study included 118 patients admitted and treated in the Department of Surgery in Al-assad University Hospital in Lattakia, 76 females (64.4%) and 42 males (35.6%). These fissures were located posteriorly in 106 cases (89.8%), anteriorly in 11 cases (9.8 %), and in the tow places in 1 case (0.8%). Patients chosen were divided into two groups. The first was treated surgically, and it included 68 patients. The second was treated by injecting the BOTOX, and it included 50 patients. Furthermore, we divided the second group into two subgroups: the first included 30 patients who received 10 IU of the BOTOX and the second included 20 patients who received 20 IU of the BOTOX. The objective of this study was to choose the most effective strategies of treating chronic anal fissures with minimum complications and risk.